REROUTING OF HIGH / RECURRENT ANAL FISTULA WITHOUT SETON: Recurrent Anal Fistula - Maqsood, Surg Capt Rasikh; Rasikh, Alia (Pakistan Armed Forces Medical Journal, 2012)
Objective: To evaluate a new treatment option in cases of high or complex anal fistulas where either the internal opening could not be outlined or there is recurrence after surgery.Study Design: Quasi Experimental study.Place and Duration of study: This study was carried out in Pakistan Naval Ship Hafeez from Jun 2008 to Aug 2011.Patients and Methods: Thirty seven patients were selected for a rerouting procedure in PNS Hafeez. The selection criteria included patients with a high or a complex fistula who had previous surgery but had recurrence of their condition. Complex fistulas, tuberculous fistulas, fistulas with two or more external openings & patients with a recurrent fistula who subsequently were found to have a low fistula were excluded from the study.The lower part of the tract was dissected, rerouted and brought out through the anal canal. The excess tract was excised and the cut end was sutured with the anal canal mucosa, thus converting an external fistula into an internal one, where the secretions from it can be retained by the external anal sphincter, thus preventing constant soiling.Results: Average age was 37 years. Thirty (81%) patients were males. Follow up period was 6 months. Tuberculosis and malignancies were ruled out. The over all success rate was 86.5%.Conclusion: Rerouting of high or recurrent anal fistulas, though not the ideal procedure, can be a useful option in cases where either the internal opening cannot be found or there has been a failure of conventional procedures. It does not eradicate the problem, but prevents constant uncontrolled discharge, which is the main concern of the patient.